FULL-WAVEFORM INVERSION IN TIME DOMAIN BY ITERATIVE FREQUENCY INCREASED - Jnanaparama Aparajita, Made
With seismic imaging techniques using numerical solutions of seismic acoustic wave equations, full-waveform inversion in the time domain can be a tool for estimating high-resolution models from complex geological conditions. However, full-waveform inversion in the time domain has several drawbacks, namely if you determine the initials of the model that is far from the global minimum (the true model) will give a stacked result at the local minimum and to overcome this problem is to use the method of increasing the frequency iteratively. With this method, at least it will keep away the results from a local minimum and close to a global minimum. The result of using the iterative frequency increment method on the full-waveform inversion time domain produces an image that resembles the original synthetic model and produces an updated velocity value that is not too different from the actual velocity value of the synthetic model